Perancangan VUI Pada Aplikasi Layanan Berita Kompas ID dengan Metode Human Centered - Tri Prastio Nugroho; Mai Candra, Reski; Insani, Fitri; Iskandar, Iwan; Affandes, Muhammad (Computer Science and Information Technology, 2024)
Digital news has become an important breakthrough in current information development, replacing printed newspapers which are increasingly less popular in Indonesia. However, the majority of digital news readers, especially on Kompas.id, are elderly, who may face difficulties in using modern technology. This raises the question of whether sophisticated digital news products are enough to address issues of accessibility and convenience for seniors. This research aims to present innovative solutions by utilizing technology Voice User Interface (VUI) to help elderly and young digital news users. MethodHuman-Centered Design (HCD) was used in this study. Result ofUsability Testing (UT) on the prototype shows that users gave a positive assessment with a total score of 91.3, a high level of satisfaction. This became the basis for continuing development of this prototype.